2021
DOI: 10.3390/s21041132
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amperometric and Potentiometric Probes in Scanning Electrochemical Microscopy for the Spatially-Resolved Monitoring of Severe Localized Corrosion Sites on Aluminum Alloy 2098-T351

Abstract: Amperometric and potentiometric probes were employed for the detection and characterization of reactive sites on the 2098-T351 Al-alloy (AA2098-T351) using scanning electrochemical microscopy (SECM). Firstly, the probe of concept was performed on a model Mg-Al galvanic pair system using SECM in the amperometric and potentiometric operation modes, in order to address the responsiveness of the probes for the characterization of this galvanic pair system. Next, these sensing probes were employed to characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This can be achieved through different means, including qualitative and quantitative approaches. The simplest method used to place the sensor tip near the substrate is by observing it with the aid of a microscope [52][53][54]. This procedure is useful for UME diameters ≥ 10 µm.…”
Section: Positioning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved through different means, including qualitative and quantitative approaches. The simplest method used to place the sensor tip near the substrate is by observing it with the aid of a microscope [52][53][54]. This procedure is useful for UME diameters ≥ 10 µm.…”
Section: Positioning Methodsmentioning
confidence: 99%
“…They observed that during the formation of the passive layer, the pH decreased and that this process was not instantaneous, as previously assumed. Da Silva et al [54] analyzed the distribution of reactive sites and local pH change during severe localized corrosion on 2098-T351 Al alloy. They observed that at the severe localized corrosion sites, there was lower pH, higher H 2 evolution, and lower O 2 consumption.…”
Section: Corrosionmentioning
confidence: 99%
“…For this generation of hydrogen to occur, it is necessary to attain a sufficiently acidic environment, which could only become achievable locally after the active release of metal cations, to a sufficient degree so that their hydrolysis can lead locally to significant acidification [55]. In fact, as the coating at edges can become thinner and even promote asymmetries due to different grain structures, these sites are more vulnerable to corrosive agents, leading to severe localized corrosion [56]. Although any of the metal cations that dissolve from the galvanized coating can undergo hydrolysis, given the strongly acidic nature of the Al 3+ cation and its accumulation at the iron-coating interface (along with Mg), this species is considered to be the most likely responsible for the local acidification:…”
Section: Electrochemical Behaviourmentioning
confidence: 99%
“…Additional analyses are needed to more precisely discern the nature and origins of such an acidification resulting in hydrogen evolution, since a microelectrochemical characterization under hydrogen gas evolution is subject to disruptive convective effects. This convection not only prevents proper SVET analysis, but SECM in generation-collection mode also becomes limited, although it has been reported to be qualitatively applicable as an approach for the determination of hydrogen evolution [29,56].…”
Section: Electrochemical Behaviourmentioning
confidence: 99%
“…Nowadays, more and more researchers pay attention to SECM [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ] due to its high spatial resolution and versatility. The ultramicroelectrode (UME) (in micro-scale or nano-scale) combined with a 3D mobile platform permits it to capture micro morphological and chemical data in situ over the interface [ 40 , 41 , 42 , 43 , 44 , 45 ]. In our earlier research, a submicron Pt/IrO x -pH UME was applied to monitor the local radial pH distribution and evolution within the gap, using the potentiometric mode of SECM [ 41 ].…”
Section: Introductionmentioning
confidence: 99%